ESTIMATION OF THE COAL ENTERPRISES INFLUENCE ON CHANGES OF PARAMETERS OF A RIVER DRAIN ON THE TERRITORY OF DONBAS - RIZNYK, T.; LIUTA, N.; SANINA, I. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2006)
Completed analysis of river flow forming conditions in highly loaded region within Donbas river basin. Shaft water dumping influence on quantitive factors of analysed territory's river flow forming estimated. Preliminary ecological estimation of this flow on Samara, Siverskiy Donets, Kalmius and Krinka rivers is given with using GIS.